Biomarkers and sociodemographic factors predicting one-year readmission among liver cirrhosis patients - Dai J; Zhao J; Du Y; McNeil EB; Chongsuvivatwong V (Dove Medical Press, 2019)
Jingyi Dai,1,2,* Jun Zhao,3,* Yingrong Du,1 Edward B McNeil,2 Virasakdi Chongsuvivatwong21Department of Liver Diseases, The Third People’s Hospital of Kunming City, Kunming, Yunnan, People’s Republic of China; 2Epidemiology Unit, Faculty of Medicine, Prince of Songkla University, Hat Yai, Songkhla, Thailand; 3School of Public Health and Management, Hubei University of Medicine, Shiyan, Hubei, People’s Republic of China*These authors contributed equally to this workBackground: Hospital readmissions of patients with cirrhosis is a current problem in China. This study aims to estimate the readmission rate at one year after discharge and to identify associated risk factors of hospital readmission.Methods: Between January 2012 and December 2015, 3,402 patients admitted with cirrhosis were included in the study. The primary outcome was one-year inpatient readmission. Principal components analysis was conducted on the laboratory test indicators to reduce the number of dimensions. Univariate and multivariate analyses were performed using clinical and demographic data to identify independent associated factors of readmission within one year. The odds ratio (OR) and 95% confidence interval were used to assess the strength of association for each factor.Results: Two dimensions, namely “liver function” and “renal function”, were revealed. Patients with a longer length of stay in the index admission (OR: 1.03; 95% CI: 1.03–1.04) and a higher dimension score of liver function (OR: 1.09; 95% CI: 1.05–1.13) were more likely to be readmitted within one-year. Older patients had a significantly higher odds of one-year readmission than younger patients (OR: 1.61; 95% CI: 1.22–2.11), patients who were married had a higher odds than those who were single (OR: 1.62; 95% CI: 1.12–2.36), and patients with hepatitis C virus were more likely to be readmitted within one year than patients with hepatitis B virus (OR: 1.51; 95% CI: 1.19–1.91).Conclusion: Biomarkers and sociodemographic factors can identify patients at high risk for readmission within one year. Our data indicates the need to emphasize proper liver care to older patients who have been hospitalized for a long time.Keywords: cirrhosis, readmission, liver function, renal function